The Specifics of the Stromal and Parenchymal Liver Components of 0–6-month-old Dead Children from HIV-monoinfected Mothers - Sherstiuk, Sergiy O.; Panov, Stanislav I.; Belozorov, Igor V.; Liadova, Tetiana I.; Tsivenko, Oleksij I. (Open Access Macedonian Journal of Medical Sciences, 2020)
OBJECTIVE: The objective of the study was to determine the specifics of the stromal and parenchymal liver components of 0–6-month-old children from HIV-monoinfected mothers. METHODS: The morphometric investigation included 84 liver tissue biopsies of 0–6-month-old dead children from HIV-monoinfected mothers. All morphometric parameters of the parenchymal and stromal liver components were calculated using the Avtandilov’s microscopic morphometric grid, which was consisted of 100 equidistant points. It was inserted into the microscope’s ocular tube with a total ×200 microscope magnification. The number of points that were found on the corresponding types of parenchymal and stromal liver components was calculated. In every case, it was selected 10 random microscopic areas and then all data were obtained, calculated, and presented as percentages. RESULTS: Morphometric parameters of hepatocytes: Mononuclear hepatocytes – 87.3 ± 6.2% (control – 93.5 ± 7.1), two-nuclear hepatocytes – 12.7 ± 1.3% (control – 6.5 ± 1.2), two-/mononuclear hepatocytes coefficient – 0.14 ± 0.01 (control – 0.06 ± 0.01), and hepatocytes with fat vacuoles – 15.6 ± 1.8% (control – 0.5 ± 0.2). Parenchymal and stromal liver components: Parenchyma – 64.3 ± 2.1% (control – 74.2 ± 1.3), stroma (including blood vessels and bile ducts) – 35.7 ± 1.9% (control – 25.8 ± 1.6), and stroma/parenchyma index – 0.55 ± 0.01 (control – 0.34 ± 0.01). Morphometric parameters of all of the liver components: Hepatocytes – 64.3 ± 3.1% (control – 74.2 ± 4.3), portal tracts – 14.9 ± 1.9% (control – 3.1 ± 0.6), central veins – 9.3 ± 1.3 % (control – 9.3 ± 1.4), sinusoids – 8.8 ± 1.1% (control – 10.5 ± 1.3), and bile ducts – 2.7 ± 0.2% (control – 2.9 ± 0.2). Expression level parameters: Fibronectin – 64.8 ± 4.1% (control – 17.3 ± 2.5), collagen Type I – 13.6 ± 1.7% (control – 9.7 ± 1.9), collagen Type III – 15.3 ± 1.4% (control – 10.1 ± 0.9), and collagen Type IV – 6.8 ± 0.2% (control – 5.9 ± 0.2). CONCLUSIONS: It was established that in the liver of 0–6-month-old dead children from HIV-monoinfected mothers, the parenchymal component of the liver showed the signs of its reduction, increase of regenerative activity of hepatocytes, and fatty degeneration of hepatocytes with a certain sign of reactive steatohepatitis. Furthermore, it was established that the stromal component of the liver of children from HIV-infected mothers showed the signs of its progressive proliferation and collagenization due to increased production and accumulation of fibronectin, Type I, Type III collagens in the stroma of portal tracts and newly formed septa, and the signs of hepatic sinusoid capillarization due to Type IV collagen accumulation in the space of Disse of the hepatic sinusoids.